Translation, pilot psychometric validation, and comparative performance of the arabic version of the Anti-Clot Treatment Scale (ACTS) - Sireen Abdul Rahim Shilbayeh; Sahar Abd El Rahman Ismail (Wolters Kluwer Medknow Publications, 2021)
Background: Anticoagulation management is a complex process that is managed through careful monitoring, and patient satisfaction has a significant impact. Given the lack of a valid and reliable tool in Arabic to examine patient satisfaction, the present study aimed to translate and examine some of the psychometric properties of the Anti-Clot Treatment Scale (ACTS) among Saudi patients. Materials and Methods: This was a cross-sectional, methodological study conducted among patients receiving warfarin. The questionnaire was subjected to translation by using a multistep method. The final Arabic translated version of the ACTS underwent face and content validity assessments by independent experts to ensure its conceptual equivalence to the original English version. Subsequently, pilot testing of convergent, discriminant, and criterion validities were examined. Results: Overall, 136 patients participated in the study. All patients were asked to complete the generic Treatment Satisfaction Questionnaire for Medication (TSQM) alongside the ACTS tool. Convergent validity analyses revealed statistically significant positive correlations (p < 0.01) between the ACTS subscales and the four TSQM subdomains, as reflected by the Spearman correlation coefficient (r). Interestingly, the strongest correlations were observed between ACTS Burdens and the TSQM convenience domain (r = 0.61) and between ACTS Benefits and the TSQM effectiveness satisfaction score (r = 0.58). Similarly, discriminant validity was evidenced by moderate to high significant loading of all 12 items on each of their corresponding ACTS subscales. Conclusion: These findings of adequate validity support the use of the ACTS in Saudi patients receiving anticoagulant medications to measure their specific satisfaction levels with this type of therapy. However, future research addressing the clinical impact of ACTS scores in the Saudi population is needed.